The poly (A) polymerase pcnB modulates virulence and resistance in Klebsiella pneumoniae by differentially regulating chromosomal mRNA stability and plasmid copy number - Zhang, Liaoqin; Zhang, Shujie; Wang, Jun; Zhang, Zhongdong; Xu, Yong; Zhang, Chen (Frontiers in Microbiology, 2025)
Klebsiella pneumoniae is a leading cause of healthcare-associated infections, with emerging strains exhibiting both multidrug resistance and hypervirulence, largely mediated by plasmid-encoded genes. Poly (A) polymerase I, encoded by pcnB, plays a key role in RNA degradation and plasmid copy number control, yet its global regulatory impact in K. pneumoniae remains unclear. Here, we constructed a pcnB deletion mutant in K. pneumoniae ATCC 13883 using CRISPR-Cas9 and examined its effects on chromosomal virulence factors and plasmid-borne resistance. Deletion of pcnB impaired bacterial growth and metabolic activity, reduced biofilm formation, but unexpectedly enhanced siderophore and exopolysaccharide production via upregulation of chromosomal virulence genes. In contrast, pcnB deletion drastically reduced the copy number and stability of a ColE1-type plasmid carrying a spectinomycin resistance gene (aadA), leading to decreased aadA expression and a twofold reduction in antibiotic resistance. These findings reveal the dual role of pcnB as a repressor of chromosomal virulence genes and an activator of plasmid maintenance, highlighting its potential as a novel target for anti-virulence and anti-resistance strategies.